(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
In recent years, tidal energy has emerged as a potential key player in future energy security, as it provides a reliable, predictable and dependable source of renewable energy, where, in 2023, the cumulative installed capacity of tidal stream energy in Europe, since 2010, reached 30.5 MW. As tidal energy strives towards commercial viability, optimisation of structural components through efficient designs is coming to the fore. The DNV-ST-0164 standard presents conservative strain limits for tidal turbine blade design in the absence of material testing. For glass-fibre laminates, tensile strain ≤ 0.35% and compressive strain ≤ │-0.25%│and, for carbon-epoxy laminates, tensile strain ≤ 0.24% and compressive strain ≤ │-0.18%│ are the limits specified. These In this paper, the results from structural testing of full-scale tidal turbine blades have been used to inform the strain failure limits mentioned in the previous section. Therefore, the conservative strain limits will be compared to those observed during the experimental testing at blade failure. This will be based on the results from a 5 metre helical blade and a 8 metre horizontal axis blade, along with a number of other large composite structures tested, where strain has been monitored close to the location of failure using contact strain gauges. An overview of the test and the key results from each of these structural testing programmes is presented in the paper, along with a discussion of the results. The observations noted in this paper, which are based on the results from a number of structural testing programmes on full-scale tidal turbine blades, which were performed in line with the IEC 62600-3:2020 test specification and the DNV-ST-0164 standard, can inform the next revision of these standards. This will aid in supporting the development of tidal energy and help lower the levelised cost of tidal energy in Europe.